2018
DOI: 10.1111/jtsb.12196
|View full text |Cite
|
Sign up to set email alerts
|

Designing social action: The impact of reflexivity on practice

Abstract: The main goal of this article is to analyse the relationship between reflexivity and action along three axes.The first entails the discussion of a reflexive action model that explores the combination of factors, processes and mechanisms which explain the guiding role reflexivity can play with regard to practices, in specific circumstances. The second axis concerns situations in which reflexivity does not act as an orientation mechanism and may even have the opposite effect, as a source of disorientation and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…At the same time, Caetano (2017) and Archer (2017) acknowledged that, while there is no direct correspondence between the two typologies, they both only partially cover individual reflexivity mechanisms, especially when it comes to heterogeneous actors. This in turn opens up the way for more empirically driven costructs of reflexivity types to be observed in particular contexts and situations (Caetano, 2015b(Caetano, , 2019.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At the same time, Caetano (2017) and Archer (2017) acknowledged that, while there is no direct correspondence between the two typologies, they both only partially cover individual reflexivity mechanisms, especially when it comes to heterogeneous actors. This in turn opens up the way for more empirically driven costructs of reflexivity types to be observed in particular contexts and situations (Caetano, 2015b(Caetano, , 2019.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the reflexivity concept has been extensively discussed by social theorists (for review, see Caetano, 2015a) who have developed several different theoretical constructs of modes (Archer, 2003(Archer, , 2007(Archer, , 2012 and different types of individuals' reflexivity (Caetano, 2017). While this paper acknowledges these theoretical constructs and related typifying[3], it follows recent calls to be open to the examination of reflexivity as an empirically driven construct (Archer, 2017;Caetano, 2015b, Caetano, 2019. In this regard, applying to the accounting domain, Aleksandrov et al (2018) proposed mapping so-called reflexivity forms (or multiple reflexivities) as different forms of empirically driven "internal conversations" revealed by the various actors during new accounting tools' development.…”
Section: Qram 171mentioning
confidence: 96%
“…However, one could easily argue that cognition and behavior are framed by a multitude of psychological and social dimensions (including norms, beliefs, knowledge and dispositions, interaction context, actors’ perceptions, appraisals, expectations and motivations, among others) [122,123]. To give a specific example, one of these processes is known as personal reflexivity, which is the capacity that individuals have to think about themselves and the world, their decisions and interactions, as well as to project future behavior [124,125,126]. The authors have found diverse profiles of personal reflexivity, framed, among others, by the individuals’ social origins.…”
Section: Linking Iron Deficiency To Cognition and Social Behavior mentioning
confidence: 99%
“…Agents may be strategically responsive, but not always knowledgeable in their actions or have intentional outcomes in mind (Burkitt, 2018;Caetano, 2019). In considering the usefulness of Archer's dualism of structure-agency in the higher education context, South African educationalist Williams (2012) maintained that it was not clear if university students believed they are agents and are able to act back on the structures around them to bring about changes to structures and their associated cultures.…”
Section: Agentsmentioning
confidence: 99%
“…In Archer's structure-agency-agents relationship, concerns are what people value or care about the most (Archer, 2012;Caetano, 2019). Values are concerns connected to our perception or sense of self and our preparedness to commit at some level to them and to determine action (Caetano, 2019). Values are wide-ranging including fairness, justice, reciprocity (Ahier et al, 2003), meaningfulness, satisfaction in life, and study-life balance (Coetzee & Oosthuizen, 2012), and are open to multiple interpretations.…”
Section: Values and Concernsmentioning
confidence: 99%